Embryonic development in corkwing wrasse, Symphodus melops. Issue 5 (10th April 2019) - Blanco Gonzalez, Enrique; Torstensnes, Ingrid; Naito, Mana
Abstract: Corkwing wrasse, Symphodus melops, is one of the main species used as cleaner fish to combat sea lice infestation in salmon aquaculture; however, there is little knowledge about its biology. Here, we describe the embryonic development of this species and examine the viability of the eggs under three temperature regimes. The experiments were conducted at three water temperature regimes, 12, 15, and 18°C, which resemble common sea water temperatures registered during the spawning season of corkwing wrasse at different latitudes along the Norwegian coast. Corkwing wrasse spawn small spherical eggs of 0.75–0.80 mm in diameter (mean 0.78, CV = 3.6%) with several oil droplets and go through eight developmental stages until hatching. The shortest hatching time was registered after 144 hr at 18°C and after 222 and 372 hr at 15 and 12°C, respectively. These observations provide important baseline biological information to advance the establishment of commercial rearing techniques and sustainable fishing management practices for this heavily exploited species.